Pediatric obstructive sleep apnea screening questionnaire and post-operative outcomes: A prospective observational study. (December 2019) - Raman, Vidya T.; Geyer, Emily; Miller, Rebecca; Tumin, Dmitry; Splaingard, Mark; Jatana, Kris R.; Tobias, Joseph D.
Abstract: Introduction: Obstructive Sleep Apnea (OSA) and Sleep Disordered Breathing (SDB) in children tend to be a more complex and multifactorial disease than in adults. Although adult screening tools, such as the STOP-BANG questionnaire, their application limited in pediatrics. We used our previously described 6-point questionnaire to identify OSA in children and evaluated its use for predicting post-operative respiratory events. Methods: Children from 3 to 18 years of age presenting for surgery were eligible. Exclusion criteria were emergency surgery or refusal to participate. A 6-question survey regarding symptoms of OSA/SDB was administered preoperatively. Neck circumference was measured. Height and weight were recorded from preoperative data and the body mass index (BMI) percentile obtained. Results: 749 patients were enrolled in the study. 707 patients were in the final analysis (359 boys and 348 girls, mean age 12 ± 4 years). The median 6-item questionnaire score was 1 (interquartile range: 0, 2) and 186 (26%) scored ≥ 2 of 6 points. Children with predicted OSA (yes on ≥ 2 questions) were more likely than without predicted OSA to require supplemental oxygen in the PACU (24% vs. 17%; 95% confidence interval [CI] of difference: −0.3%, 13%; p = 0.049). Amongst 681 patients with available data on Post Anesthesia Care Unit (PACU) length of stay (LOS), prolonged LOS (>1 h) was not more likely among children with predicted OSA (42%) compared to those without predicted OSA (39%; 95% CI of difference: −5%, 11%; p = 0.479). Outcomes assessed after PACU discharge noted no differences. Specifically, overnight hospital stay was required in 33% of patients with predicted OSA as compared to 29% of those without (95% CI of difference: −4%, 11%; p = 0.399). On POD 0, supplemental oxygen was used on the inpatient ward for 6% of patients with predicted OSA compared to 4% of patients without predicted OSA (95% CI of difference: −2%, 6%; p = 0.272). Conclusion: The incidence of OSA/SDB is under-appreciated in children presenting for non-otolaryngological surgical procedures. Although patients judged to have OSA on the 6-item question may need for supplemental oxygen longer in the PACU, no other outcomes differences were noted.